Improved Exposition Text Reading Ability By Using Problem Based Learning Students In SMP Negeri 3 Lahewa In 2020 - Merliana Zendrato (UMSU, 2020)
Learning to Read Exposition Text with Problem Based Learning Model in Junior High School. This study aims to describe the process and results of learning to read exposition text using problem-based learning mode. Research designed with classroom action research. The data used in this study are data on the implementation process in the form of observations, field notes, and documentation, as well as evaluation data which includes the results of the reading test for the exposition text using a problem-based learning model. The data is sourced from grade VIII students of SMP Negeri 3 Lahewa. The results of this study indicate that the reading skills of the exposition text have increased significantly